The New South - Griffing, May Lucetta (My University, 1907)
Introduction: The New South! What a study is this New Southland of ours! Mushroomlike, but faintly seen one evening, but grown overnight into a full sized beneficial article. This New south is a New South in every sense of the word, built under new conditions, looked at in a new light, new institutions, character and principles must be painfully yet faithfully remodeled. It is a South most radically different from that of 1860. Many of the changes are for the better, a few for the worse.
Citation: Griffing, May Lucetta. The New South. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: The American South; Post-Civil War South; Reconstruction Era; Theses; Manuscripts (documents)